2014
DOI: 10.1186/cc13964
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine – from conditionally essential to totally dispensable?

Abstract: Recently a large multicentre randomised controlled trial in critically ill patients reported harm to the patients given supplementary glutamine. In the original publication, no explanation was offered for why this result was obtained; a large number of studies have reported beneficial effects or no effect, but never before reported harm. These results have been commented upon in a number of communications. Now some of the authors of the multicentre randomised controlled trial present a review and meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…These findings contradict the hypothesis that glutamine is a conditional essential amino acid during critical illness [5]. …”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…These findings contradict the hypothesis that glutamine is a conditional essential amino acid during critical illness [5]. …”
Section: Discussioncontrasting
confidence: 89%
“…It has been suggested that supplementation with immune-modulating nutrients should be reserved for specifically identified patients with compromised availability and plasma levels should be measured before supplementation [5]. However, low plasma levels could reflect adaptive and beneficial stress responses rather than conditional deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Acute fulminant liver failure is therefore regarded a contraindication for glutamine substitution during critical illness [ 11 , 12 ]. It is less clear if patients with chronic and acute-on-chronic liver failure should also be exempted from glutamine supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…According to them there are not recommendations for routine use of Gln in all patients of intensive care units [ 51 , 52 , 53 , 54 , 55 ]. Therefore, Gln use in intensive care patients is also controversial [ 57 , 58 ].…”
Section: Glutamine (Gln)mentioning
confidence: 99%